Initial Outcome of Surgical Management of Parotid Gland Neoplasm - Sumon, Mohammad Misbah Al Kabir; Afsana, Sultana Dil; Hossain, Md Belal (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Surgical excision is the gold standard for treatment of parotid gland neoplasm. But the complex relationship of the tumour to the facial nerve in the parotid gland makes the surgery very challenging. Objective: To evaluate the initial outcome of parotid gland neoplasm surgery. Materials and Methods: This cross-sectional observational study was conducted from January to December 2012 where 20 surgically treated patients with parotid gland neoplasm were selected by random sampling technique. They were followed up from 03 to 06 months to assess the minor post-operative complications. Results: The study revealed that 35% of patients belonged to the 4th decade of life. Pleomorphic adenoma constituted 85% of the tumours. Superficial parotidectomy was performed in 95% of cases. 40% of patients developed neuropraxia of the marginal mandibular branch of the facial nerve but all improved over a period of 3-6 months. 5% had permanent facial nerve weakness. Frey’s syndrome was observed in 20% of cases clinically but improved gradually. The rate of wound infection, parotid fistula and hypoesthesia of the skin over the ear lobule occurred in 10%, 5% and 20% cases respectively. Conclusion: Safe and effective parotid gland surgery requires a clear understanding of the regional anatomy, the experience of the surgeon, meticulous surgical technique along with detailed preoperative informed consent for surgery to reduce post-operative complications and morbidity of the patient. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 193-195